2011
DOI: 10.1085/jgp.201110608
|View full text |Cite
|
Sign up to set email alerts
|

Mutant cycles at CFTR’s non-canonical ATP-binding site support little interface separation during gating

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride channel belonging to the adenosine triphosphate (ATP)-binding cassette (ABC) superfamily. ABC proteins share a common molecular mechanism that couples ATP binding and hydrolysis at two nucleotide-binding domains (NBDs) to diverse functions. This involves formation of NBD dimers, with ATP bound at two composite interfacial sites. In CFTR, intramolecular NBD dimerization is coupled to channel opening. Channel closing is triggered by hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 60 publications
6
54
0
Order By: Relevance
“…This model envisages "limited motions" of the NBD dimer in the completion of one catalysis (and gating) cycle. Of note, this model is supported by a report that employed a completely independent approach (Szollosi et al 2011). The significance of this new model lies in the fact that all members of the ABCC subfamily possess only one catalysis-competent site in their NBDs.…”
Section: Roles Of Nbd Dimerization In Cftr Gatingmentioning
confidence: 61%
“…This model envisages "limited motions" of the NBD dimer in the completion of one catalysis (and gating) cycle. Of note, this model is supported by a report that employed a completely independent approach (Szollosi et al 2011). The significance of this new model lies in the fact that all members of the ABCC subfamily possess only one catalysis-competent site in their NBDs.…”
Section: Roles Of Nbd Dimerization In Cftr Gatingmentioning
confidence: 61%
“…The P o for each subsequent condition was then calculated by dividing the NP o product measured for that condition by this value. Second, stationary noise analysis was used to estimate P o s from multichannel records as previously described for CFTR (30, 31). This method is based on the premise that the currents that are mediated by channels with high P o s exhibit less variance (σ 2 ) than those mediated by channels with lower P o s, which gate more dynamically.…”
Section: Methodsmentioning
confidence: 99%
“…This method is based on the premise that the currents that are mediated by channels with high P o s exhibit less variance (σ 2 ) than those mediated by channels with lower P o s, which gate more dynamically. For each current record, the mean current (m) and the current variance (σ 2 ) were obtained from Clampfit after the baseline noise was subtracted (30, 31). The P o for each patch was estimated from these parameters using the equation μ (1 – P o ) = σ 2 /i , where i is the unitary current at the experimental holding potential (–0.4 pA at –60 mV for WT‐CFTR).…”
Section: Methodsmentioning
confidence: 99%
“…This model was also supported by a report employing an independent approach. By studying the energetic coupling between different residue pairs located around ABP1, Szollosi et al (69) found that the coupling energy between these residue pairs does not change throughout the gating cycle. Since each pair tested includes one residue in the head of NBD1 and the other in the tail of NBD2, these results indicate that interaction of two NBDs around ABP1 remains static during gating.…”
Section: Fishing the “Invisible” Kinetic Statesmentioning
confidence: 99%
“…Since each pair tested includes one residue in the head of NBD1 and the other in the tail of NBD2, these results indicate that interaction of two NBDs around ABP1 remains static during gating. (69). Of note, like CFTR, many members in the ABC protein family contain only one catalysis-competent site (32, 39, 52, 72).…”
Section: Fishing the “Invisible” Kinetic Statesmentioning
confidence: 99%